The Performance of Integrated Health Service and Nutritional Status of Children Under Five in Padang Pariaman Subdistrict, West Sumatera - . Kasmita; Ali Khomsan; Dadang Sukandar; Djoko Susanto (Media Gizi dan Keluarga, 2000)
The objectives of the study were to analyze performance of integrated health service (Posyandu) and nutritional status of children under five. A cross-sectional study was conducted in Padang pariaman, West Sumatera. Thirty Posyandu and 934 children were sampled. The Posyandu’s performance sata were: carde characteristics, knowledge, and participation. The nutritional status of children was measured using anthropometry. Activities of Posyandu Purnama and Mandiri were better compared to Posyandu Pratama and Madya. Nutritional knowledge of cadre was relatively similar among Posyandus, and so was the participation. The nutritional status of children at the three categories Posyandu was not diffrence (p>0,05). Cadre needs improvement of nutrition knowledge and shills.Keywords: children, nutritional status, Posyandu.